Physicians’ knowledge, attitudes, and beliefs regarding practices of male and female surgical sterilization procedures in Lebanon - Jad Najdi; Alexandre Armache; Elia Abou Chawareb; Nassib Abou Heidar; Marwan Zein; Anthony Fadel; Jimmy Nehme; Bassel Bachir (Contraception and Reproductive Medicine)
Abstract Objective Surgical sterilization, including vasectomy in males and tubal ligation in females, is a highly effective but underutilized contraception method. Adoption rates vary globally mostly due to misconceptions by both the general public and practicing physicians. Our survey aims to explore physicians’ knowledge, attitudes and beliefs about surgical sterilization techniques in Lebanon. Study design A web-based survey was sent to residents and attending physicians of different specialties in Lebanon between April 2022 and April 2023. The survey included 21 multiple-choice questions divided in four parts (demographics, knowledge, attitudes and beliefs) and required around 8 min to complete. Data was analyzed using IBM SPSS Statistics. A descriptive analysis was performed using the chi-square test for categorical variables and ANOVA for continuous variables. Results One hundred eighty-three physicians specialized in Urology, OB/GYN, Family medicine and Internal medicine filled the survey. The majority were resident physicians (79%), male (57%), single (72%) and did not receive training in family planning (73%). Knowledge assessment showed an average score of 5/7. After setting this as a passing score, 60.7% of participants passed the assessment with higher likelihood of passing among attending physicians (84.6%), OB/GYN physicians (94.4%), married participants (80.8%), and physicians who received training in family planning (91.8%). Lower likelihood of passing was among Family Medicine (60%), and Internal Medicine (72.5%) physicians. Recommendations varied among specialties. Most physicians perceived the general public preferring tubal ligation as a sterilization method (98%). Conclusion Lebanese primary care physicians have a lower level of knowledge of surgical sterilization procedures compared to specialists. This, coupled with low levels of family planning training and negative perception of patient beliefs may impact attitudes and recommendations. Ongoing education and family planning training is needed to increase awareness among physicians, especially primary care physicians, to allow them to provide more adequate counseling to patients.